Synthetic Biology and Morality : Artificial Life and the Bounds of Nature - Kaebnick, Gregory E. (Book collections on Project MUSE., 2013)
Synthetic biology, which aims to design and build organisms that serve human needs, has potential applications that range from producing biofuels to programming human behaviour. The emergence of this new form of biotechnology, however, raises a variety of ethical questions - first and foremost, whether synthetic biology is intrinsically troubling in moral terms. Is it an egregious example of scientists 'playing God'? This book takes on this key ethical question, as well as others that follow, offering a range of philosophical and political perspectives on the power of synthetic biology.